2016
DOI: 10.1016/j.chom.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infects Human Placental Macrophages

Abstract: SUMMARY The recent Zika virus (ZIKV) outbreak in Brazil has been directly linked to increased cases of microcephaly in newborns. Current evidence indicates that ZIKV is transmitted vertically from mother to fetus. However, the mechanism of intrauterine transmission and the cell types involved remain unknown. We demonstrate that the contemporary ZIKV strain PRVABC59 (PR 2015) infects and replicates in primary human placental macrophages, called Hofbauer cells, and to a lesser extent in cytotrophoblasts, isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
456
2
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 440 publications
(497 citation statements)
references
References 28 publications
29
456
2
10
Order By: Relevance
“…Although there are fundamental differences between the approach of the two groups (such as use of current endemic virus versus high passage historic strains, measurement of -strand RNA rather than + strand RNA, and the duration of both infectivity and culture), the findings are not necessarily conflicting. Existing data supports a model in which trophoblast production of type III interferons might inhibit ZIKV infection 9 . Using a low-passaged current endemic ZIKV strain, primary human trophoblasts were shown to be permissive to low levels of ZIKV replication 9 .…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Although there are fundamental differences between the approach of the two groups (such as use of current endemic virus versus high passage historic strains, measurement of -strand RNA rather than + strand RNA, and the duration of both infectivity and culture), the findings are not necessarily conflicting. Existing data supports a model in which trophoblast production of type III interferons might inhibit ZIKV infection 9 . Using a low-passaged current endemic ZIKV strain, primary human trophoblasts were shown to be permissive to low levels of ZIKV replication 9 .…”
supporting
confidence: 55%
“…Existing data supports a model in which trophoblast production of type III interferons might inhibit ZIKV infection 9 . Using a low-passaged current endemic ZIKV strain, primary human trophoblasts were shown to be permissive to low levels of ZIKV replication 9 . However, this study used Hofbauer cells (macrophages present in the placental chorionic villi) that supported log-fold viral growth ex vivo relative to cytotrophoblasts.…”
supporting
confidence: 55%
“…The significance of the occurrence of Hofbauer cell proliferation and hyperplasia, together with the demonstration of residual virus in these stromal cells following transplacental fetal infection, is especially interesting in light of a recent investigation that has demonstrated that Zika virus can experimentally infect, and subsequently replicate in, human Hofbauer cells. In this study, Quicke et al 43 found that Hofbauer cells isolated from term human placentas were permissive to infection by a contemporary strain of Zika virus that is currently circulating in the Americas. Following in vitro infection of Hofbauer cells by Zika virus, viral replication was documented in these cells, which was accompanied by induction of type I interferon and proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, damage to STB, for example, by herpes simplex virus (58), or transcytosis of ZIKV across STB by piggybacking on an Ig directed against another flavivirus, such as one of the DENV serotypes (18,59), could be other causes of fetal ZIKV infection beyond the first trimester and reasons for geographical and socioeconomic differences in fetal susceptibilities. Whole villi dissected from placentas at different stages of pregnancy and cultured in the presence of ZIKV certainly become infected (57,58,60,61), but STB remains largely unscathed. In the in vitro trophoblast system derived from term placenta, it also seems possible that infection Unlike trophoblast derived from term placentas, ESC differentiated under BAP conditions for 4 d, which we suggest is analogous to the primitive trophoblast of the early first trimester, are highly susceptible to infection by ZIKV U .…”
Section: Release Of Infection-competent Virus By Esc and Esc-derived mentioning
confidence: 99%